Fluxos de capitais com viés de curto prazo e vulnerabilidade externa do Brasil no período 2000-2014 - Pereira, Vanessa de Paula (2015)
The aim purpose of this Dissertation is to study, through Brazil s analysis, the external vulnerability specificity of the periphery countries, considering, for this, the financial part of the Balance of Payment. The paper s central hypothesis is that Financial Account matter in the vulnerability research; the greater short-term foreign capital, the higher external vulnerability potential is. This, because, both, Balance of Payment and Net Foreign Liability, are adverse impacted. From the Balance of Payment view, foreign investment makes periphery countries more vulnerable by its two accounts. From Financial Account point of view, increasing the flows volatility potential; to the side of Current Account, sending income to foreign countries. From Net Foreign Liability perspective, the vulnerability is perceived by the rise of liability stock, which is more onerous when it has short-term profile. The Brazilian studies shows that the greatest contributors to the national vulnerability potential are: Foreign Portfolio Investment (equity and debt) and Nonresident Direct Investment Equity Capital; all of them strongly influenced by global market dynamic, especially by the VIX index. Besides, another crucial results of the research is the acknowledgement that, unlike of the current literature shows, part of Direct Investment is speculative and has a similar (and influenced) dynamic with portfolio investment.